Winter wheat cultivar post‐harvest effects: Varieties differ in residue management requirements and effect on yield of next crop - Ryan C. Graebner; Kyle Harrison; Matthew Hunt; Daisy Wood; Christina H. Hagerty (Agrosystems, Geosciences & Environment)
Abstract This study investigated the potential of different wheat varieties to influence the performance of the subsequent wheat crop. In fall 2021, a single variety of winter wheat (cv. Norwest Tandem) was planted into standing wheat stubble in plots that were previously planted to five winter wheat varieties. At harvest, yield was significantly affected by the variety that had been planted in each plot during the first year of the trial. Specifically, wheat following the variety Pritchett yielded approximately 12% more than wheat following the variety Bobtail. While planting the second crop, residue from the winter wheat variety Norwest Duet caused the no‐till plot drill to plug (accumulate large amounts of soil and crop residue in front of openers) far more than residue from the other varieties. This indicates that varieties differ in their residue management requirements. These differences could be exploited to best fit different agricultural practices. This study highlights the potential importance of varietal effects that persist in the field after the field is harvested. However, more work is needed to understand varietal differences in residue management requirements and varietal effects of the successive crop before they can be fully leveraged in wheat breeding and genetics, wheat agronomy, variety testing programs, and eventually the producer's field.